MODERN EDUCATION IN THE CONTEXT OF INTER-CIVILIZATIONAL RELATIONS - Ashytok, Nadiia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2023)
Introduction. The current stage of human development requires the education system to review the worldview principles aimed at finding commonalities between civilizations, co-evolutionary strategies for the interaction of communities, nature, and society, focused on cooperative relations between people in particular, and civilizations in general. That is why research is relevant in that education is considered as a resource capable of improving tolerant relations between civilizations. The aim of the article is to understand the current state of education in the context of inter-civilizational relations. The task is to analyze the works that talk about the existence of modern sociocultural communities and to outline the educational problems that arise on the basis of the features of contemporary intercivilizational relations. Research methods are general scientific and special methods and approaches used for the study of education in the context of inter-civilizational relations, one of which is a systematic approach aimed at revealing the integrity of pedagogical objects (inter-civilizational relations in the field of education), identifying various types of connections in them, and unifying into a single theoretical picture. Research results. Modern social consciousness considers education an external factor. The external factor is subordinated to the internal one, according to which the idea of the value of education as a life strategy is established in the social consciousness. To study the internal factor, an axiological approach is appropriate, in the context of which the value differences between civilizations are investigated as the reason for their possible collisions of a threatening nature. In the context of intercivilizational relations, the actualization of education problems is due to the reassessment of values and the search for the content of universal human identity. A manifestation of the revaluation of values was the activation of the civilizational vision of the world as the unity of diversity, including in the field of education, on the basis of common human tasks and values. Nowadays, holistic education is being created, which is based on the integration of different types of worldview as equal, complementary, and partnership. Discussion. The process of rapid civilizational progress will not cover all humanity equally for a long time. And therefore expect the formation of the specified type of education in all countries of the world. However, a prerequisite for weakening the confrontation is already being created, which is education in the spirit of peace and cooperation, understanding the shared fate of humanity, tolerance, and respect. Conclusions. The convergence of education systems will contribute to the convergence of states, peoples, cultures, and civilizations on the basis of axiological commonality, that is, the sphere of basic values and higher goals. This gives rise to the hope that civilizations, despite significant differences, will converge in the spiritual sphere, and this will help avoid the possible self-destruction of humanity.